Challenges of poverty alleviation through social work interventions - Willya Achmad (Institute of Computer Science (IOCS), 2024)
This research aims to analyze the challenges faced in efforts to eradicate poverty through the implementation of social work intervention programs. This research uses a qualitative approach with descriptive methods. The research results show that the concept of social work intervention at the micro, mezzo and macro levels makes a significant contribution to poverty alleviation efforts. Social workers at the micro level are able to form deep partnerships with clients, develop personalized intervention plans, and provide individualized support, which has an impact on improving individual and family well-being. At the mezzo level, collaboration in the development of community welfare programs and resource mobilization results in significant change on a broader scale. At the macro level, a focus on structural transformation and system improvement has a positive impact on overall social impact. The integration of these strategies forms a robust support network that empowers individuals and drives sustainable social change. The results of this research confirm that a holistic approach in Social Work Intervention has an important role in creating a more just, inclusive and just society in overcoming poverty.